Exploring the Low and High MassExtremes in the Distant Universe. - Feinstein, Adina D. (Tufts Archival Research Center, 2018)
By studying galaxies at different redshifts, .i.e. periods of cosmic time, astronomers can combine observations and simulations to piece together the whole story. Because it is easier to find more massive, brighter sources farther away, there is an inherent bias in our observations. TheHubbleSpace Telescope combined with the gravitational lensing power of six massive galaxy clusters, known as theHubbleFrontier Fields (HFF) Campaign, has been able to uncover the faintest and least massive known galaxies at great distances.The work I present here calculates and corrects for the lensing magnifications for sources observed in the HFF catalogs. Additionally, I will examine the most massive (M∗[M]≥1011) galaxies at 2≤z≤6 from the extensive, multi-wavelength UltraVISTA survey. By studying both the lowest and highest mass objects in the distant universe, we can further study galaxy evolution as a function of galactic mass.